Analisis Kinerja Keuangan Berdasarkan Rasio Profitabilitas Pada Lembaga Perkreditan Desa (Lpd) Desa Pakraman Banyuning - Devi, Luh Intan Pardina; Pasek, Gede widiadnyana (Universitas Pendidikan Ganesha, 2021)
This study aims to determine how the development of financial performance use Profitability Ratio is Return on Equity (ROE) at Lembaga Perkreditan Desa (LPD) Desa Pakraman Banyuning. The subject of this research is Lembaga Perkreditan Desa (LPD) Desa Pakraman Banyuning and the object of research is analysis of financial performance based on profitability ratio. The types of data used are quantitative and qualitative data. Data collection methods in this study are interviews and documentation. The data of Analysis used is descriptive quantitative analysis. The result of this study indicate that financial performance at Lembaga Perkreditan Desa (LPD) Desa Pakraman Banyuning is good enough because it has reached the ratio standard. Development of Return on Equity (ROE) at Lembaga Perkreditan Desa (LPD) Desa Pakraman Banyuning from 2016 to 2020 produced at average of 18,85% and had met the standards set is 12,5%, the ratio achieved showed the companyâ€™s condition was in HEALTHY group. The higher the yield, the better because the dividends distributed or reinvested as retained earnings are also greater.Â Â